2016
DOI: 10.1111/modl.12330
|View full text |Cite
|
Sign up to set email alerts
|

Development of Thinking for Speaking: What Role Does Language Socialization Play?

Abstract: It has been noted that Chinese shows both satellite‐ and verb‐framed properties (Beavers, Levin, & Tham, ; Slobin, ), a fact that offers the opportunity to explore the typological influence of learners’ dominant language because they can choose either option to describe the same motion events and be grammatically correct. This study comprehensively examined the impact of factors including the dominant language's thinking for speaking (TFS) (Slobin, , , ), as well as proficiency and degree of socialization with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 52 publications
(90 reference statements)
0
20
0
Order By: Relevance
“…Although the majority of the participants were from the high-proficiency groups, the L2 learners' online processes of listening-for-imagery seemed to indicate that they had not yet totally internalized the L2-specific deictic paths in their L2 TFS, even with advanced proficiency. While L2 learners were able to produce motion language following L2 TFS patterns in the mode of writing or speaking as reported in previous studies (e.g., [5,7,8]), scrutinization of the online automatic processing of the motion language in the mode of "listening for imagery" may reveal a different story. On the other hand, the results of this study were in agreement with findings reported in Yoshioka and Kellerman [45], Choi and Lantolf [46], and Stam [47], in which they also examined the co-speech gesture produced by the L2 learners and found no sign of switching to L2 TFS (cf.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Although the majority of the participants were from the high-proficiency groups, the L2 learners' online processes of listening-for-imagery seemed to indicate that they had not yet totally internalized the L2-specific deictic paths in their L2 TFS, even with advanced proficiency. While L2 learners were able to produce motion language following L2 TFS patterns in the mode of writing or speaking as reported in previous studies (e.g., [5,7,8]), scrutinization of the online automatic processing of the motion language in the mode of "listening for imagery" may reveal a different story. On the other hand, the results of this study were in agreement with findings reported in Yoshioka and Kellerman [45], Choi and Lantolf [46], and Stam [47], in which they also examined the co-speech gesture produced by the L2 learners and found no sign of switching to L2 TFS (cf.…”
Section: Discussionmentioning
confidence: 58%
“…Although English speakers naturally run mental simulations of objects moving toward them when processing motion sentences such as The car approached you, automatic activation of simulation in processing Chinese deictic paths lái 'hither' or qù 'thither' proved to be a domain of L2-specific TFS patterns for English-speaking learners that had not yet been salient enough to be noted when the learners were listening to the motion sentences. Echoing Wu [8,40], it was reported that L2 learners of both HLL and FLL backgrounds produced significantly less deictic paths when describing motion scenes, as compared to Chinese NSs.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Daller et al, 2011;Stam, 2010Stam, , 2015. Wu (2016) found that heritage language learners performed better in supplying target-like motion patterns than foreign language learners at the same proficiency level.…”
Section: Crosslinguistic Influence In the Acquisition Of Motion Expre...mentioning
confidence: 99%
“…Previous studies on L2 acquisition of Chinese DCs discovered that the difficulty of learning literal DCs comes from the syntactic complexity of their constructions (Qian, 1997;Wu, 2011;Yang, 2003) and the typological features of Chinese (Wu, 2011). Most of these studies examined learners' production of literal DCs by employing production tasks such as oral narrative (e.g., Wu, 2016). Little is known about learners' acquisition of figurative DCs and their comprehension of literal and figurative DCs.…”
Section: Introductionmentioning
confidence: 99%